La ocupación cazadora-recolectora durante la transición Pleistoceno-Holoceno en el oeste de Rio Grande do Sul - Brasil : geoarqueología de los sitios en la formación sedimentaria Touro Passo - Vidal, Viviane Pouey (Archaeopress Publishing Ltd, 2018)
This work presents the results obtained during geoarchaeological studies carried out in the locality of Touro Passo, Brazil. New chronologies obtained represent a scientific advance for the study of hunter-gatherer occupations during the Late Pleistocene-Early Holocene in the triple border of Brazil, Argentina, and Uruguay.